A Smart Intracellular Self‐Assembling Bioorthogonal Raman Active Nanoprobe for Targeted Tumor Imaging - Swati Tanwar; Behnaz Ghaemi; Piyush Raj; Aruna Singh; Lintong Wu; Yue Yuan; Dian R. Arifin; Michael T. McMahon; Jeff W. M. Bulte; Ishan Barman (Advanced Science, 2023)
Abstract Inspired by the principle of in situ self‐assembly, the development of enzyme‐activated molecular nanoprobes can have a profound impact on targeted tumor detection. However, despite their intrinsic promise, obtaining an optical readout of enzyme activity with high specificity in native milieu has proven to be challenging. Here, a fundamentally new class of Raman‐active self‐assembling bioorthogonal enzyme recognition (nanoSABER) probes for targeted tumor imaging is reported. This class of Raman probes presents narrow spectral bands reflecting their vibrational fingerprints and offers an attractive solution for optical imaging at different bio‐organization levels. The optical beacon harnesses an enzyme‐responsive peptide sequence, unique tumor‐penetrating properties, and vibrational tags with stretching frequencies in the cell‐silent Raman window. The design of nanoSABER is tailored and engineered to transform into a supramolecular structure exhibiting distinct vibrational signatures in presence of target enzyme, creating a direct causality between enzyme activity and Raman signal. Through the integration of substrate‐specific for tumor‐associated enzyme legumain, unique capabilities of nanoSABER for imaging enzyme activity at molecular, cellular, and tissue levels in combination with machine learning models are shown. These results demonstrate that the nanoSABER probe may serve as a versatile platform for Raman‐based recognition of tumor aggressiveness, drug accumulation, and therapeutic response.